ORIENTAL CALLIGRAPHY IN ART PEDAGOGY - Zhukova, Kateryna; Rudaya, Nataliia; Ozerska, Oksana; Naumenko, Stanislav; Zub, Olena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Nowadays, the art of calligraphy is being revived. Computer typing, has largely replaced handwritten version, however it cannot develop fine motor skills, memory training, and concentration. Thus, a person does not receive a certain training set necessary for the harmonious development of brain activity. In recent years, the direction of "calligraphy therapy" has been developing, which is precisely aimed at filling the missing skills. In modern pedagogy, inclusive education comes to the fore in importance. Methods of working with people with special needs are being developed, including the direction of "art pedagogy", that is, learning through art. And it is precisely oriental (art) calligraphy (Chinese, Japanese), which is a whole philosophy and art that has developed over many centuries, that can fully meet new pedagogical tasks. The article proposes the concept of a new method of inclusive education - "art calligraphy", which can be used as one of the elements of art pedagogy for working with people with special needs.